Optimum Tilt Angle at Tropical Region - Soulayman, S; Sabbagh, W (Center of Biomass & Renewable Energy, Diponegoro University, 2015)
: One of the important parameters that affect the performance of a solar collector is its tilt angle with the horizon. This is because of the variation of tilt angle changes the amount of solar radiation reaching the collector surface. Meanwhile, is the rule of thumb, which says that solar collector Equator facing position is the best, is valid for tropical region? Thus, it is required to determine the optimum tilt as for Equator facing and for Pole oriented collectors. In addition, the question that may arise: how many times is reasonable for adjusting collector tilt angle for a definite value of surface azimuth angle? A mathematical model was used for estimating the solar radiation on a tilted surface, and to determine the optimum tilt angle and orientation (surface azimuth angle) for the solar collector at any latitude. This model was applied for determining optimum tilt angle and orientation in the tropical zones, on a daily basis, as well as for a specific period. The optimum angle was computed by searching for the values for which the radiation on the collector surface is a maximum for a particular day or a specific period. The results reveal that changing the tilt angle 12 times in a year (i.e. using the monthly optimum tilt angle) maintains approximately the total amount of solar radiation near the maximum value that is found by changing the tilt angle daily to its optimum value. This achieves a yearly gain in solar radiation of 11% to 18% more than the case of a solar collector fixed on a horizontal surface.